2016
DOI: 10.3390/su8080714
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pig Slurry as Basal and Panicle Fertilizer on Trace Element Content and Grain Quality in Direct-Seeding Rice

Abstract: Direct-seeding rice has grown in popularity in recent years and is widespread in China. This study focused on the effects of pig slurry (PS) on grain quality and safety in direct-seeding rice. Application of more than 210 m 3¨h m´2 increased rice yield and dry matter accumulation, compared with conventional chemical fertilizer treatment (CK2). At the heading and maturing stage, a high dosage of PS (T6, T8 and T9 treatments) promoted uptake of Pb, Cu, Zn, Fe and Mn by rice plants and grain, but retarded uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…MN17, provides a cost-effective, environmentally friendly way of increasing yield and of reducing the Cd content of pea plants growing in Cd-contaminated soil. These results support published studies on other species showing that organic and inorganic soil amendments and microbial inoculation can improve plant growth on heavy metal contaminated soil [12,15,33,[44][45][46]. Amongst the properties of biochar and gravel sand are that they adsorb Cd onto their surfaces and make it less available to plant roots [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…MN17, provides a cost-effective, environmentally friendly way of increasing yield and of reducing the Cd content of pea plants growing in Cd-contaminated soil. These results support published studies on other species showing that organic and inorganic soil amendments and microbial inoculation can improve plant growth on heavy metal contaminated soil [12,15,33,[44][45][46]. Amongst the properties of biochar and gravel sand are that they adsorb Cd onto their surfaces and make it less available to plant roots [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…The shorter growing season often leads producers in colder regions to apply larger amounts only one or two times per season. Conversely, regions with longer growing seasons may apply fertilizer, both manure and synthetic, more often at smaller rates, effectively reducing N losses without a yield penalty, thereby improving N use efficiency (Huang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The use of PS as a nutrient source for rice cultivation could be a form of local supply with high reserves that would allow recycling and reduce management problems associated with increasing local livestock waste. Some studies have reported the potential use of PS as an alternative fertilizer for rice ( Pan et al., 2009 ; Huang et al., 2016 ; Moreno-García et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%